Enhanced photocatalytic activity of silver vanadate nanobelts in concentrated sunlight delivered through optical fiber bundle coupled with solar concentrator - Roy, Joy Sankar [UNESP]; Dugas, Gabriel; Morency, Steeve; Ribeiro, Sidney J. L. [UNESP]; Messaddeq, Younes [UNESP] (Springer, 2020)
To date, sunlight driven photocatalytic process for wastewater treatment is a great challenge. Herein, the photocatalytic methylene blue (MB) dye degradation activity of silver vanadate nanobelts has been enhanced using concentrated sunlight irradiation. The MB dye degradation factor in normal and concentrated sunlight irradiation is 0.57 and 0.25 respectively after 120 min of light exposure. Therefore, degradation of MB dye in concentrated sunlight occurs more than two times faster than normal sunlight. The silver vanadate nanobelts have been prepared by simple hydrothermal method. The prepared nanobelts are very thin having length ranging between 5 and 10 mu m and width is in the 100-300 nm range. The optical band gap of the synthesized silver vanadate nanobelts is 1.96 eV (632.5 nm), which indicates strong absorption of visible light. This work will open new technological aspects for cost-effective sustainable wastewater treatment using solar energy.
Keywords: Silver vanadate; Sunlight driven photocatalysis; Concentrated sunlight; Solar concentrator; Optical fiber; Water purification